Identification of high-impact gene–drug pairs for pharmacogenetic testing in Alberta, Canada. Issue 2 (February 2021) - Fan, Mikayla; Yarema, Mark C.; Box, Adrian; Hume, Stacey; Aitchison, Katherine J.; Bousman, Chad A.
Abstract : Objectives: To facilitate decision-making and priority-setting related to Alberta's Pharmacogenomics (PGx) testing implementation strategy by identifying gene–drug pairs with the highest potential impact on prescribing practices in Alberta. Patients and methods: Annual drug dispensing data for Alberta from 2012 to 2016 for 57 medications with PGx-based prescribing guidelines were obtained, along with population estimates and demographics (age and ethnicity). Frequencies of actionable PGx genotypes by ethnicity were obtained from the Pharmacogenomics Knowledgebase (PharmGKB). Annual dispensing activity for each of the 57 medications was calculated for the full population (all ages) and children/youth (0–19 years). Alberta ethnicity data were cross-referenced with genetic frequency data for each of the main ethnic groups from PharmGKB to estimate the proportion of individuals with actionable genotypes. Actionable genotype proportions and drug dispensing frequencies were collectively used to identify high impact gene–drug pairs. Results: We found (a) half of the drugs with PGx-based prescribing guidelines, namely, analgesics, proton pump inhibitors, psychotropics, and cardiovascular drugs, were dispensed at high frequencies (>1% of the entire population), (b) the dispensing rate for about one-third of these drugs increased over the 5-year study period, (c) between 1.1 and 45% of recipients of these drugs carried actionable genotypes, and (d) the gene–drug pairs with greatest impact in Alberta predominatly included CYP2C19 or CYP2D6 . Conclusions: We uncovered specific patterns in drug dispensing and identified important gene–drug pairs that will inform the planning and development of an evidenced-based PGx testing service in Alberta, Canada. Adaptation of our approach may facilitate the process of evidence-based PGx testing implementation in other jurisdictions. Abstract : Supplemental Digital Content is available in the text.